2020
DOI: 10.3390/fi12060100
|View full text |Cite
|
Sign up to set email alerts
|

Patient Privacy Violation Detection in Healthcare Critical Infrastructures: An Investigation Using Density-Based Benchmarking

Abstract: Hospital critical infrastructures have a distinct threat vector, due to (i) a dependence on legacy software; (ii) the vast levels of interconnected medical devices; (iii) the use of multiple bespoke software and that (iv) electronic devices (e.g., laptops and PCs) are often shared by multiple users. In the UK, hospitals are currently upgrading towards the use of electronic patient record (EPR) systems. EPR systems and their data are replacing traditional paper records, providing access to patients’ test result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The implementation of technology in the healthcare domain increases the probability of exposing sensitive health data [48]. It is one of the top three sectors that face the highest number of breached incidents annually [61]. Boddy et al discuss healthcare data confidentiality and specify that both the insider as well as outsider threats violate healthcare data confidentiality and results in patients' loss of trust in the healthcare service providers [45,57].…”
Section: Rq2 Does the Study Discuss Healthcare Data Confidentiality Issues?mentioning
confidence: 99%
“…The implementation of technology in the healthcare domain increases the probability of exposing sensitive health data [48]. It is one of the top three sectors that face the highest number of breached incidents annually [61]. Boddy et al discuss healthcare data confidentiality and specify that both the insider as well as outsider threats violate healthcare data confidentiality and results in patients' loss of trust in the healthcare service providers [45,57].…”
Section: Rq2 Does the Study Discuss Healthcare Data Confidentiality Issues?mentioning
confidence: 99%
“…Contrary to these propositions, the work performed by Ge et al [43] while aiming to predict disease by using deep learning also assured the data deletion approach by the data owner to limit access to their health data. Toward the identification of anomalous behaviors within electronic patient record (EPR) datasets, researchers Hurst et al [44] presented an investigation methodology. e proposed framework uses the LOF algorithm to detect unusual data patterns, labeling points as normal or anomalous, under the consideration of an HIL approach.…”
Section: Centralized Architecturementioning
confidence: 99%
“…A sample of the raw EHR data is displayed in Table 1 for clarification. The disaggregation of the EHR is a necessary step for benchmarking normal and anomalous behaviours for each of the four action groups in the record for the supervised learning; as the core activities within each of the groupings differ to a high extent -as outlined in detail in previous work (Hurst et al, 2020).…”
Section: Anomaly Detection Approachmentioning
confidence: 99%
“…Few other approaches use real world data on this scale and many adopt simulation for testing; yet none have tested the approach on this specific dataset. For clarity, the data used for the analysis is provided by a UK-based hospital (which the authors have made available on EASY-DANS (Hurst, 2021)), with the anomalous readings pre-labelled by means of density-based classification outlined in our related work in (Hurst et al, 2020) where anomalous points were confirmed in verbal consultation. 2) The focus of this approach is on insider threats, rather than external, and specifically focused on EHR datasets.…”
Section: Introductionmentioning
confidence: 99%